A middle-aged man with a troubled liver: Combination therapy in advanced (BCLC Stage C) hepatocellular carcinoma - Zamri Zuhdi; Azlanuddin Azman; Affirul Chairil Ariffin; Razman Jarmin; Hairol Azrin Othman (Archives of Clinical and Experimental Surgery, 2018)
Advanced hepatocellular carcinoma carries a bad prognosis with a survival of only few months. Barcelona Clinic Liver Cancer (BCLC) Guidelines recommended sorafenib monotherapy as the treatment modality for advanced BCLC Stage C disease, citing a two-month increase in survival rates. Here, we highlight a case with advanced HCC (BCLC Stage C) treated with combination therapy of liver resection and Sorafenib therapy. The patients current survival rate was beyond 10 months. We also discuss the current evidence on liver resection with Sorafenib therapy in hepatocellular carcinoma. The description of the case may benefit in future diagnosis and treatment. [Arch Clin Exp Surg 2018; 7(1.000): 29-32]